A Systematic Review and Meta-Analysis of Prostate Cancer Utility Values of Patients and Partners Between 2007 and 2016. Issue 1 (May 2019) - Magnus, Anne; Isaranuwatchai, Wanrudee; Mihalopoulos, Cathrine; Brown, Victoria; Carter, Rob
Background. There is widespread agreement that both the length and quality of life matter when assessing new technologies and/or models of care in the treatment for cancer patients. Quality of life for partners/carers also matters, particularly for prostate cancer.Purpose. This systematic review aims to provide up-to-date utility values along the prostate cancer care continuum (i.e., from prescreening through to palliative care) for use where future trial-based or modelled economic evaluations cannot collect primary data from men and/or partners.Data Sources. A protocol was developed and registered on the international register of systematic reviews—PROSPERO. Databases searched included EBSCO Information Services (CINAHL, EconLit, Global Health, HEED, MEDLINE Complete, PsycINFO), Cochrane Database of Systematic Reviews, Web of Science, and Embase.Study Selection. Study selection terms included health-related quality of life, prostate cancer, and partners or carers.Data Extraction. The authors identified articles published between 2007 and 2016 that provided health state utility values, with statistical uncertainty, for men with or at risk of prostate cancer and/or their partner/carers.Data Synthesis and Results. Study quality and generalizability of utilities was evaluated and meta-analysis conducted against prespecified criteria. From 906 original articles, 29 recent primary studies met the inclusion/exclusion criteria. We tabulate all the utility values with uncertainty, along with considerable methodological detail and patient population characteristics.Limitations. Utility values pertaining to carers/partners were limited to one study.Conclusions. Studies varied in design, measurement instruments utilized, quality, and generalizability. There is sufficient qualitative and quantitative detail for the reported utility values to be readily incorporated into economic evaluations. More research is needed with carers/partners and with newly developing prostate cancer-specific quality of life tools.